Exploiting salivary miR-375 as a clinical biomarker of oral potentially malignant disorder - Hsi-Feng Tu; Li-Han Lin; Kuo-Wei Chang; Hui-Wen Cheng; Chung-Ji Liu (Elsevier, 2022)
Background/purpose: Oral potentially malignant disorder (OPMD) is an important premalignancy worldwide. MicroRNAs (miRNAs) are endogenously expressed non-coding RNAs that regulate the post-transcriptional levels of targeted mRNAs. MiRNA-375 (miR-375) is markedly downregulated in oral carcinoma tissues and plays an oncogenic role in oral carcinogenesis. We explored the potential of the deregulated salivary miR-375 levels in OPMD patients. Materials and methods: . We analyzed the levels of miR-375 in the saliva of patients with OPMD (n = 45) and healthy controls (n = 24) by quantitative RT-PCR. The cell lysates and supernatants were treated with the miR-375 mimic and inhibitor. Results: Salivary miR-375 levels were decreased markedly in the patients with OPMD, compared with the controls. OPMD patients with non-dysplasia showed a higher abundance of miR-375 in the saliva than dysplasia patients, suggesting that salivary miR-375 is a more sensitive marker for OPMD. Patients with malignant transformation during the follow-up period showed lower expression of saliva miR-375 than the others. MiR-375 expression was markedly decreased by treatment with the miR-375 inhibitor, and the supernatants of both NHOK and SAS cells showed a corresponding decline in miR-375 expression. Conclusion: Our results indicate the potential application of salivary miR-375 as a biomarker for the detection and long-term follow-up of OPMD.